Optimizing Cadres of Gerbek Paru (Pulmonary Case Elimination Movement) in Padureso Village Jumo District, Temanggung Regency, Indonesia - Sri Hananto Ponco Nugroho; Kusminarti Kusminarti; Tri Novia Widyastuti; Sani Widayanti (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Indonesia is one of the countries with the highest TB cases in the world. There are 845,000 cases with a mortality rate of 98,000 or equivalent to 11 death per hour. Data from the control and eradication of infectious diseases section (P2PM) of Tumenggung Health Office indicated that TB case-finding in Temanggung is still far from the predetermined targets. In 2021, from 1490 targets, it was achieved 8046 TB suspects. The results also showed that both TB case-finding and suspects findings were below the targets. Therefore, this activity aimed to eliminate TB in Padureso village. The activity was carried out by the following methods: socialization, counselling and training, and accompaniment. First, the socialization was held with partner. Then, training was conducted in terms of contact investigation, TB suspects screening, and sputum sample delivery with internal courier. Next, accompaniment included TB treatment through drug supervisors (PMO), finding and treating TB patients until cure (TOSS TB), demonstrations of effective coughing, glass tile installation for nonstandard houses of TB patients, as well as the overall activity. This activity has optimized cadres’ knowledge and roles to achieve TB elimination.